Facing the enemy [large type] - Mills, DiAnn (Center Point Large Print, 2023)
"For the past five years, FBI Special Agent Risa Jacobs has worked in the violent crimes against children division of the Houston FBI. She's never had reason to believe there's a target on her back. . . until now. When the long-awaited reunion between Risa and her brother, Trenton, ends in tragedy, Risa is riddled with guilt, unable to cope with the responsibility she feels over his death. On leave from the FBI, Risa returns to her former career as an English teacher at a local college, only to see her past and present collide when one of her students, Carson Lowell, turns in an assignment that reads like an eyewitness account of her brother's murder, with details never revealed publicly. Alarmed by Carson's inside knowledge of Trenton's death, Risa reaches out to her former partner at the FBI. Special Agent Gage Patterson has been working a string of baby kidnappings, but he agrees to help look into Carson's background. Risa and Gage soon discover their cases might be connected as a string of high-value thefts have occurred at properties where security systems were installed by Carson's stepfather and children have gone missing. There's a far more sinister plot at play than they ever imagined, and innocent lives are in danger."--